Determinant factors in climbing ability: Influence of strength, anthropometry, and neuromuscular fatigue - Laffaye, G.; Levernier, G.; Collin, J.-M. (Scandinavian Journal of Medicine & Science in Sports, 2016)
The goal of this study was to (i) assess the physical and anthropometric differences between three levels of climbers and (ii) predict climbing ability by using a multiple regression model. The participants were divided into novice (n = 15), skilled (n = 16), and elite (n = 10) climbers. Anthropometric characteristics such as height, weight, percentage of body fat and muscle, bi-acromial breath, arm span, and ape index were measured. General and specific strength were assessed through an arm jump test, a bench press test, and a hand and finger grip strength test in maximal and endurance conditions. All variables were combined into components via a principal component analysis (PCA) and the components used in a multiple regression analysis. The major finding of this study is that climbing ability is more related to specific rather than general strength. Only finger grip strength shows a higher level of initial strength between all samples while the arm jump test discriminates between climbers and non-climbers. The PCA reveals three components, labeled as training, muscle, and anthropometry, which together explain 64.22% of the variance. The regression model indicates that trainable variables explained 46% of the total variance in climbing ability, whereas anthropometry and muscle characteristics explain fewer than 4%.